Measuring Corporate Social Responsibility: A Scale Development Study - Turker, Duygu (Journal of business ethics, 2009)
Corporate social responsibility (CSR) is one of the most prominent concepts in the literature and, in short, indicates the positive impacts of businesses on their stakeholders. Despite the growing body of literature on this concept, the measurement of CSR is still problematic. Although the literature provides several methods for measuring corporate social activities, almost all of them have some limitations. The purpose of this study is to provide an original, valid, and reliable measure of CSR reflecting the responsibilities of a business to various stakeholders. Based on a proposed conceptual framework of CSR, a scale was developed through a systematic scale development process. In the study, exploratory factor analysis was conducted to determine the underlying factorial structure of the scale. Data was collected from 269 business professionals working in Turkey. The results of the analysis provided a four-dimensional structure of CSR, including CSR to social and nonsocial stakeholders, employees, customers, and government.